Алгоритми балансування навантаження в Грід-системах - Petrenko, A. I.; Svistunov, S. Ya.; Svirin, V. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The analysis of strategies of balancing load in the Grid-systems and comparative analysis of existing algorithms of the distribution of flow of the tasks between computing resources of a Grid environment are shown.